A novel Ehrlichia strain (Rickettsiales: Anaplasmataceae) detected in Amblyomma triste (Acari: Ixodidae), a tick species of public health importance in the Southern Cone of America - Cicuttin, Gabriel L.; De Salvo, María Nazarena; Díaz Pérez, Paula; Silva, Darío; Félix, María Laura; Venzal, José Manuel; Nava Santiago (Taylor & Francis, 2020)
The aim of this work was to report the detection of a putative novel Ehrlichia strain associated with the tick Amblyomma triste. Free-living adult ticks determined as A. triste were collected by drag-sampling in Argentina and Uruguay. Molecular detection of Ehrlichia agents was performed targeting three different loci: 16S rRNA gene, dsb gene and a fragment of groESL heat shock operon. In total, 164 adults of A. triste (38 from INTA E.E.A Delta del Paraná in Argentina and 126 from Toledo Chico in Uruguay) were analyzed. One tick (0.6%) collected in INTA E.E.A. Delta del Paraná (Argentina) was positive. The phylogenetic analyses show that the Ehrlichia strain found in this study (named Ehrlichia sp. strain Delta) represents an independent lineage within the genus Ehrlichia, close to E. chaffeensis and E. muris. This is also the first report of an Ehrlichia agent infecting the tick A. triste. The medical and veterinary significance of Ehrlichia sp. strain Delta remains to be demonstrated. However, it is important to mention that adults of A. triste are aggressive to humans and domestic mammals. Therefore, the potential role of A. triste in the transmission of Ehrlichia agents to humans or domestic animals across its distributional range should be highlighted, even more considering that Ehrlichia sp. strain Delta is phylogenetically related to the zoonotic E. chaffeensis, which is recognized as pathogenic to both humans and animals.